Administration of assessment instruments during the first rehabilitation of patients with spinal cord injury: a retrospective chart analysis. Issue 4 (April 2018) - Lampart, Patricia; Gemperli, Armin; Baumberger, Michael; Bersch, Ines; Prodinger, Birgit; Schmitt, Klaus; Scheel-Sailer, Anke
Abstract Study design Retrospective chart analysis. Objectives To examine which professionals administered which assessment instruments in which patient in clinical practice during first rehabilitation after newly acquired spinal cord injury (SCI) and the differences in the frequencies of different assessments between patient groups. Setting Specialized SCI acute care and rehabilitation clinic. Methods Patients after SCI, aged 18 years and above, admitted for first rehabilitation between December 2014 and December 2015 were analyzed. Descriptive statistics of 54 selected assessments.p values based on theχ 2 test were calculated for assessments used in both paraplegic and tetraplegic patients. Results One hundred and nineteen patients were screened. Forty-one assessments were administered, of which 10 on average more than once per patient. The most frequently used assessments were Spinal Cord Independence Measure III (7.7 times per patient), Skin Assessment (3.6 times), and Manual Muscle Test (3.2 times for Lower Extremities; 2.5 times for Upper Extremities). The American Spinal Injury Association Impairment Scale was administered on average 1.9 times per patient. More variation in the number of assessments per patient was observed in patients with complete and incomplete lesions compared to patients with paraplegia and tetraplegia. Conclusion Assessments covering neurological functioning, mobility, and self-care are used in clinical practice during first rehabilitation of patients with SCI, while others covering autonomic functioning, pain, participation, or quality of life are still missing. Based on these observations and national and international requirements, a meaningful standard for an assessment toolkit, applicable in general and in specific subgroups, needs to be defined and implemented.